Rifampin-resistant/multidrug-resistant Tuberculosis in Alberta, Canada: Epidemiology and treatment outcomes in a low-incidence setting. - Brett D Edwards; Jenny Edwards; Ryan Cooper; Dennis Kunimoto; Ranjani Somayaji; Dina Fisher (PLoS ONE, 2021)
Treatment of rifampin-monoresistant/multidrug-resistant Tuberculosis (RR/MDR-TB) requires long treatment courses, complicated by frequent adverse events and low success rates. Incidence of RR/MDR-TB in Canada is low and treatment practices are variable due to the infrequent experience and challenges with drug access. We undertook a retrospective cohort study of all RR/MDR-TB cases in Alberta, Canada from 2007-2017 to explore the epidemiology and outcomes in our low incidence setting. We performed a descriptive analysis of the epidemiology, treatment regimens and associated outcomes, calculating differences in continuous and discrete variables using Student's t and Chi-squared tests, respectively. We identified 24 patients with RR/MDR-TB. All patients were foreign-born with the median time to presentation after immigration being 3 years. Prior treatment was reported in 46%. Treatment was individualized. All patients achieved sputum culture conversion within two months of treatment initiation. The median treatment duration after culture conversion was 18 months (IQR: 15-19). The mean number of drugs utilized during the intensive phase was 4.3 (SD: 0.8) and during the continuation phase was 3.3 (SD: 0.9) and the mean adherence to medications was 95%. Six patients completed national guideline-concordant therapy, with many patients developing adverse events (79%). Treatment success (defined as completion of prescribed therapy or cure) was achieved in 23/24 patients and no acquired drug resistance or relapse was detected over 1.8 years of median follow-up. Many cases were captured upon immigration assessment, representing important prevention of community spread. Despite high rates of adverse events and short treatment compared to international guidelines, success in our cohort was very high at 96%. This is likely due to individualization of therapy, frequent use of medications with high effectiveness, intensive treatment support, and early sputum conversion seen in our cohort. There should be ongoing exploration of treatment shortening with well-tolerated, efficacious oral agents to help patients achieve treatment completion.